Tomographic characteristics of thick corneas - Junjie Yu; Ye Xu; Xiaoying Wang; Yishan Qian (BMC Ophthalmology)
Abstract Purpose To investigate the tomographic characteristics of corneas with excessive thickness and to explore their potential impact on the assessment of candidates for refractive surgery. Methods One hundred and two eyes from 102 patients with the thinnest pachymetry (TP) < 500 μm, 100 eyes from 100 patients with TP ranging from 500 to 580 μm, and 102 eyes from 102 subjects with TP ≥ 580 μm were included. Pentacam ectasia indices were compared among these different groups. Results When compared to eyes with TP between 500 and 580 μm, significantly higher values in anterior radius of curvature (ARC), anterior corneal astigmatism (KAp), back elevation at the thinnest pachymetry (BE), deviation of normality of the back elevation (Db), and a more negative Q value for the back surface (Qback) were observed in eyes with TP ≥ 580 μm (Mann-Whitney U test: P < 0.001). No significant differences were observed in the indices for the anterior cornea (Mann-Whitney U test: index of height decentration, P = 0.348; inferior-superior value, P = 0.334; keratoconus percentage index, P = 0.077; deviation of normality of the front elevation, P = 0.891). The proportion of abnormalities was highest in eyes with TP ≥ 580 μm for BE (16.7%, Chi-square test: P < 0.001) and Db (20.6%, Chi-square test: P = 0.001). Conclusions The tomography of thick corneas reveals greater BE and Db, as well as a more negative Qback while no significant disparities emerged in the anterior corneal indices.